Accurate 5 Accounting Application Training for Students of SMA Negeri 2 Lembang, West Bandung Regency - Hasanah Tisna Amijaya; Ganjar Nurul Fajar; Rinawati Rinawati (LPPM STMIK Mardira Indonesia, 2024)
The Head of the Study Program, lecturers, and the Accounting Computerization Student Association of STMIK Mardira Indonesia's Class of 2020 and 2021 have formed a community service team to tackle the problem of SMAN 2 Lembang students' need for comprehension when it comes to using applications The team's primary focus in this project was creating and instructing accounting students on how to utilize the Accurate 5 Accounting Application. This project's primary goal is to increase students' comprehension of and proficiency with accounting software, which is crucial for equipping them with obstacles in the workplace. Practice-based learning and practical training are the approaches employed. The project has led to a notable improvement in the student's comprehension and proficiency with the Accurate 5 Application. In conclusion, SMAN 2 Lembang students' technical abilities have improved significantly due to this community service project, particularly in the area of digital accounting, and it is anticipated that these gains will last for a long time.